Sex Differences in Trauma and Posttraumatic Stress Disorder A Quantitative Review of 25 Years of Research. [article]. - Tolin, David, F.
Meta-analysis of studies yielding sex-specific risk of potentially traumatic events (PTEs) and posttraumatic stress disorder PTSD indicated that female participants were more likely than male paricipants to meet criteria for PTSD, although they were less likely to experience PTEs. Female participants were more likely than male participants to experience sexual assaults and child sexual abuse, but less likely to experience accidents, nosexual assaults, witnessing death or injury, disaster or fire, and combat or war. Among victims of specific PTEs (excluding sexual assaults or abuse), female participants exhibited greater PTSD. Thus, sex differences in risk of exposure to particular types of PTE can only partially account for the differential PTSD risk in male and female participants. -- (from the author)